Fatigue crack growth in notched specimens: a numerical analysis: Fatigue crack growth in notched specimens (Fracture and Structural Integrity, 2019)
Fatigue crack growth (FCG) is linked to irreversible and non-linear processes happening at the crack tip, which explains different problems observed in the use of da/dN-DK curves. The replacement of DK by non-linear crack tip parameters, namely the crack tip opening displacement (CTOD) is an interesting alternative. The objective in here is to study the effect of notches on FCG using the plastic CTOD range, dp. M(T) specimens with lateral notches of different radius (1, 2 4 and 8 mm were analysed numerically, keeping the total depth constant (8 mm). The increase of crack length increases dp and therefore FCG rate. For plane stress state, the formation of the residual plastic wake with crack propagation produces crack closure which compensates the effect of crack length and there is a stabilization of dp. The reduction of notch radius increases dp for all crack lengths, particularly for the shortest ones. For plane strain state there is almost no crack closure therefore dp is higher than for plane stress state, and the effect of crack length produces a relatively fast increase of dp
Keywords: Fatigue crack growth; Notches; Plastic CTOD; Crack closure